Synergistic effect of phase structures and in situ sintering of silver fillers on thermal conductivity of epoxy/polyethersulphone/silver filler composites. (3rd May 2021) - Kishi, Hajime; Saruwatari, Takashi; Mototsuka, Takemasa; Tanaka, Sanae; Kakibe, Takeshi; Matsuda, Satoshi
Abstract: The thermal conductivity of the diglycidyl ethers of bisphenol-A (DGEBA)/4, 4′-diaminodiphenylmethane (DDM)/polyethersulphone (PES)/silver (Ag) filler composites has been investigated. The DGEBA/DDM/PES blend as the matrix for the polymer composites formed co-continuous phase structures at the micrometer scale via reaction-induced phase separation during the curing process. The Ag fillers were selectively localized in the epoxy-rich phases, and consequently the fillers experienced more opportunities for contact within the narrow self-assembled templates. As the result, sintering of the Ag fillers occurred at the surface during curing, especially in the post-curing process at 180 °C. Curve-fitting of the thermal conductivity data for the composites using an extended Bruggemann's equation clarified the differences in the in situ sintering at the two curing temperatures. The synergistic effect of the phase structures of the polymer blend matrices and the in situ sintering of Ag fillers accounted for the enhanced thermal conductivities of the polymer composites. Graphical abstract: Image 1 Highlights: Thermal conductivity of epoxy/polyethersulphone/Ag-filler composites were studied. In situ sintering of Ag-filler occurred in epoxy-rich phase during post-curing at 180 °C. Synergistic effect of phase structures and sintering of Ag accounted for enhanced thermal conductivity.